Persistent Post‐Traumatic Brain Injury Hiccups Unresponsive to Standard Agents: Resolution Associated With Levetiracetam Therapy - Rostom Karajeh; Ranya Abu Khalaf; Mostafa Ibraheem Abo Alrob; Saif Khaled Abdalhadi Azzam; Youssef Abdelqader Alsaeed (Clinical Case Reports, 2026)
ABSTRACT Post‐traumatic hiccups are an uncommon but distressing complication of traumatic brain injury (TBI), often resistant to conventional pharmacological agents, and the underlying mechanism may involve central neurological disruption of inhibitory pathways rather than gastrointestinal or metabolic aetiologies. We report a male patient in his early 30s who developed refractory hiccups following moderate TBI sustained in a high‐impact motor vehicle collision; standard agents including chlorpromazine, metoclopramide, and haloperidol provided no meaningful relief after 48 h of combined treatment. Intravenous levetiracetam (1000 mg loading dose followed by 500 mg every 12 h) was initiated on hospital Day 6, which was followed by complete resolution of hiccups within 8 h; the patient was discharged on hospital Day 7 without recurrence and remained symptom‐free at two‐week outpatient follow‐up. This case highlights levetiracetam as a promising rescue therapy for post‐TBI hiccups refractory to conventional agents, possibly by modulating aberrant central neural circuitry, and further prospective studies are warranted to establish standardized treatment protocols for this challenging and underrecognised condition.